2021
DOI: 10.1111/pace.14374
|View full text |Cite
|
Sign up to set email alerts
|

Early rhythm‐control ablation therapy to prevent atrial fibrillation recurrences: Insights from the CHARISMA Registry

Abstract: Background: An early, comprehensive rhythm-control therapy is needed in order to treat atrial fibrillation (AF) effectively and to improve ablation outcomes.Methods: A total of 153 consecutive patients from the CHARISMA registry undergoing AF ablation at eight centers were included. Patients with de novo PVI were classified as having undergone early treatment (ET) if the procedure was performed within 6 months after the first AF episode, and as having undergone delayed treatment (DT) if ablation was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the AF patients enrolled in the CABANA trial who also had clinically diagnosed heart failure, catheter ablation also showed superiority for improvements in survival and quality of life when compared with medical therapy [ 27 ]. Previous studies have verified that early rhythm control therapy leads to a lower risk of cardiovascular complications in AF patients [ 29 , 30 , 31 ]. Emerging clinical evidence has also indicated that percutaneous left atrial appendage occlusion is a safe and effective therapeutic strategy for cardioembolic stroke prevention in non-valvular AF patients [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the AF patients enrolled in the CABANA trial who also had clinically diagnosed heart failure, catheter ablation also showed superiority for improvements in survival and quality of life when compared with medical therapy [ 27 ]. Previous studies have verified that early rhythm control therapy leads to a lower risk of cardiovascular complications in AF patients [ 29 , 30 , 31 ]. Emerging clinical evidence has also indicated that percutaneous left atrial appendage occlusion is a safe and effective therapeutic strategy for cardioembolic stroke prevention in non-valvular AF patients [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 However, postablation arrhythmia could relapse in at least 20% to 40% of patients after initially successful ablation in the first year. 24 , 25 , 26 In a recent small‐sample RCT, Kishima et al showed that tofogliflozin, a type of SGLT2i drug, achieved greater suppression of AF recurrence in patients with diabetes after CA. 14 A similar conclusion was also drawn in 2 other retrospective studies, as the use of SGLT2i among patients with AF and comorbid diabetes undergoing ablation was associated with lower incidence of AF recurrence comparing to those without SGLT2i.…”
Section: Discussionmentioning
confidence: 99%
“… 18 However, a significant limitation of this approach is the absence of tissue feedback during lesion creation, which results in a blunt “one‐size‐fits‐all” approach. 25 Encouraging results with a novel technology that measures LI through mini‐electrodes on the tip of a dedicated ablation catheter both in an acute setting 9 , 11 , 26 and on arrhythmia recurrence during long‐term follow‐up 10 , 27 have been recently reported. However, without intraprocedural guidance regarding where existing lesions are most vulnerable to reconnection, it is difficult to improve on these results.…”
Section: Discussionmentioning
confidence: 99%